Gondolunk még piroschkára?az ich denke oft an piroschka szerepe a németek magyarságképében: PIROSCHKA IN THE GERMANS’ IMAGE OF HUNGARIANS - Újváry, Gábor (Közép-Európai Közlemények, 2020)
The German writer Hugo Hartung’s book „Ich denke oft an Piroschka” was first published in 1954. In the first two decades after the Second World War it was the best selling literary work in the Federal Republic of Germany. Between 1954 and 1962 almost 1,2 million copies was sold. From the novel a highly successful movie was made, one of the greatest blockbuster of West German film production. Due to the many different adaptations of the book (radio play, drama, audiobook) the Piroschka story still lives on in the 21st century. Beyond the fact that the book plot takes place in Hungary, primarily at Székkutas which is beside Hódmezővásárhely, why are these works important for us Hungarians? Our response: the book had a very significant impact on the formation of a positive image of Hungarians in Germany. The jaunty, nice, not too deep, but readable novel became a true bestseller, which determinately influenced the conceptions of Hungarians in a positive way. The current study discusses these matters.